Exploring the trade-off between leaning against credit and stabilizing real activity - Luca Benati (University of Bern, Department of Economics, 2022)
Evidence from monetary VARs for ten countries points towards an unfavorable trade-off between leaning against credit fluctuations and stabilizing real economic activity. Results are robust both across countries, and based on two alternative approaches, i.e. either (i) focusing on the impact of monetary policy shocks, which I identify based on a combination of zero and sign restrictions, or (ii) analyzing 'modest' policy interventions in which the central bank reacts weakly, but systematically, to credit fluctuations. In particular, a modest intervention suggests that in the U.S. during the years leading up to the financial crisis a 1% shortfall in real GDP would have been associated with a decrease in credit leverage by 2.5 percentage points.
Keywords: 330; Credit; structural VARs; sign restrictions; zero restrictions; Lucas critique